Exploring the effects and mechanisms of organophosphorus pesticide exposure and hearing loss - Zou, Mingshan; Huang, Mao; Zhang, Jianyun; Chen, Rong (Frontiers in Public Health, 2022)
Many environmental factors, such as noise, chemicals, and heavy metals, are mostly produced by human activities, and easily induce acquired hearing loss. Organophosphorus pesticides (OPs) constitute a large variety of chemicals and have a high usage, a long half-life and potentiate healthy damage. Moreover, their metabolites, also showed the ability of contamination of soil, water and air, leading to server damage effect. Hearing loss affect 430 million people (5.5% of the global population), generating heavy burden to society and family. However, the potential risk of hearing damage by OPs has not been taken seriously. In this paper, we summarize the effects of OPs on hearing loss from both epidemiological studies and animal experiments. Further, the possible mechanisms of OPs-induced hearing loss are elucidated from oxidative stress, DNA damage and inflammatory response. Overall, this review provides an overview of the OPs exposure alone or with noise that lead to hearing loss in human and experimental animals.